HLA-B*13:01 as a Risk Allele for Antiepileptic Drugs-Induced Cutaneous Adverse Reactions: Higher Risk for Cross-Reactivity? - Min, Fu-Li; Mao, Bi-Jun; Zheng, Zhong-Zheng; He, Na; Fan, Cui-Xia; Cai, Rui-Yan; Wang, Juan; Ou, Yang-Mei; Qin, Bing; Liao, Wei-Ping; Yi, Yong-Hong; Li, Ze; et al. (Frontiers in Neurology, 2019)
Antiepileptic drugs frequently cause cutaneous adverse reactions (cADRs). Numerous studies have reported associations between human leukocyte antigen (HLA) alleles and cADRs caused by single antiepileptic drug in Southern Han Chinese people. However, the relationship between the HLA allele and cADRs sequentially induced by two or more antiepileptic drugs (AEDs-induced cross-reactivity) is unclear. To explore the associations between HLA alleles and AEDs-induced cross-reactivity, we prospectively recruited patients with AEDs-induced cross-reactivity from 2009 to 2017 and performed high-resolution genotyping to detect the HLA-A, B, C, and DRB1 alleles in patients for comparison with normal controls. To verify the important genotype, we compared its presence in patients with cross-reactivity to enlarged normal controls, and its presence in patients with carbamazepine (CBZ)-induced maculopapular exanthema (MPE) to CBZ-tolerant controls. Further, the important allele was replicated by meta-analysis. Twenty-three patients with AED-induced cross-reactivity and 500 healthy individuals were enrolled from Southern China. All patients had a mild rash without mucosal or systemic involvement. The HLA-B*13:01 allele was present in 34.78% (8/23) of patients, 14.60% (73/500) of healthy individuals, and 14.5% (763/5,270) healthy individuals, revealing a significant association (8/23 vs. 73/500; P = 0.02; OR: 3.12; 95% CI: 1.28–7.62; 8/23 vs. 763/5,270; P = 0.014; OR: 3.15; 95% CI: 1.33–7.46). HLA-B*13:01 was presented numerically higher in CBZ-induced MPE than that in CBZ-tolerant individuals without statistical significance (33/145, 22.76%, vs. 28/179, 15.64%; P = 0.103). Meta-analysis revealed an association between HLA-B*13:01 and cADRs induced by single AEDs or/and non-AEDs in Chinese and Thai populations (P = 0.000). This study suggests that HLA-B*13:01 is potentially associated with AED-cADRs in general, possibly with stronger effect in cross-reactivity. Screening for HLA-B*13:01 prior to starting AEDs therapy may help to avoid cADRs. However, this association requires further analysis in a multi-center study with a larger sample size.